Análisis financiero de la Cooperativa de Ahorro y Crédito Marcabelí Ltda., de la provincia de El Oro, periodo 2021-2022 - Salgado Suquilanda, Marcela Ivanoba (2024)
Currently, globalization and constant technological development have directly impacted the financial health of companies, organizations and financial institutions, so it is essential to have evaluation tools that allow correct and guided decisions to be made under a previous study, as is the case of this study, which is focused on developing the financial analysis of the Cooperativa de Ahorro y Crédito Marcabelí Ltda, of the province of El Oro, period 2021 - 2022, where a mixed approach was considered since it will be qualitative and quantitative. In addition, the deductive and inductive methods were applied to the financial statements provided by the institution, including the parent agency and six branches of the cooperative. As a result of vertical and horizontal analysis and the indicators provided by the CAMEL methodology, a number of main results were obtained, including positive increases and positive variations in assets and income; however, these were not enough to counteract the expenses incurred in 2022 that caused a loss of $854,303.77. The company was able to meet its obligations in 2021, however, its profitability levels and several of the financial indicators considered were not representative. The data analyzed indicate that the cooperative has depended significantly on external financing to carry out long-term projects. This strategy, although it has allowed investments to be made, has generated tensions in its financial situation during the periods studied. It is therefore recommended that new income sources be explored and a more in-depth analysis of the profitability of the investments be conducted in order to ensure their sustainability and avoid negative effects during their implementation.